Stochastic resilience enables particle foraging in oligotrophic marine environments - Vicente I. Fernandez; Natasha Blitvic; Johannes M. Keegstra; Roman Stocker (Proceedings of the National Academy of Sciences, 2026)
Heterotrophic bacteria play a central role in attenuating the sequestration of carbon to the deep ocean by degrading sinking marine particles. The role of certain copiotrophic adaptations such as surface attachment and motility in particle degradation has remained unclear outside of coastal regions, where the sparsity of particles would appear to preclude a foraging lifestyle based on particle hopping. We show here instead that many oligotrophic marine environments are much more amenable to copiotrophic particle foraging than would be inferred from average-based estimates, because the foraging process samples a broad distribution of particle–bacteria interactions, with large variation in encounter times, particle sizes, and associated survival outcomes, and due to the disproportionate benefit of a particle encounter. We develop a generalized branching process model for particle foraging to assess environment viability and population growth rates based on encounters with particles, for different oceanographic particle size spectra. The results indicate that even bathypelagic environments can support particle foraging bacteria without requiring long-term starvation tolerance or multiyear feast–famine cycles, because stochastic encounters generate sufficient short-interval, high-reward events to sustain population growth despite long mean encounter times. More generally, stochasticity can confer resilience to microbial populations in resource-scarce marine environments.